2016
DOI: 10.1007/978-3-319-43624-1_10
|View full text |Cite
|
Sign up to set email alerts
|

N6-Methyladenine: A Conserved and Dynamic DNA Mark

Abstract: Chromatin, consisting of deoxyribonucleic acid (DNA) wrapped around histone proteins, facilitates DNA compaction and allows identical DNA code to confer many different cellular phenotypes. This biological versatility is accomplished in large part by post-translational modifications to histones and chemical modifications to DNA. These modifications direct the cellular machinery to expand or compact specific chromatin regions, and mark regions of the DNA as important for cellular functions. While each of the fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(64 citation statements)
references
References 215 publications
(282 reference statements)
2
62
0
Order By: Relevance
“…1a). 5mC (+ 3mC) levels ranged from between 1.7-7% in all of the more recently evolved eukaryotes examined, but was not detected in three yeast species, S. pombe, S. cerevisiae, and S. japonicus, as previously reported [3] ( Fig. 2b).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…1a). 5mC (+ 3mC) levels ranged from between 1.7-7% in all of the more recently evolved eukaryotes examined, but was not detected in three yeast species, S. pombe, S. cerevisiae, and S. japonicus, as previously reported [3] ( Fig. 2b).…”
Section: Resultssupporting
confidence: 82%
“…Directed DNA methylation by specific methyltransferase enzymes occurs in both prokaryotes and eukaryotes. These modifications can mark regions of the genome for control of a variety of processes, including base pairing, duplex stability, replication, repair, transcription, nucleosome positioning, X-chromosome inactivation, imprinting, and epigenetic memory [1][2][3]. The most well studied and abundant DNA methylation in eukaryotes is 5mC, a mark typically associated with repressed chromatin that occurs on~3-8% of cytosines in mammals [4].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from 5mC, the most common types of enzyme-catalysed DNA modifications include N4-methylcytosine (4mC) and N6-methyladenine (6mA), which are widespread across bacteria. Notably, 6mA is also found in varying amounts in eukaryotes 30 and has recently been implicated in TE regulation in Drosophila melanogaster and mice 31,32 , although the presence and functional relevance of 6mA in higher eukaryotes remains controversial [33][34][35] . Moreover, 5mC can be oxidized by teneleven translocation (TET) enzymes to 5-hydroxymethylcytosine (5hmC), 5-formylcytosine (5fC) and 5carboxylcytosine (5caC), as part of a replication-independent pathway to DNA demethylation ( Figure 3).…”
Section: [H1] Introductionmentioning
confidence: 99%
“…To address this, we exploited N6-methyladenine (m6A). In contrast to cytosine methylation, which is abundant in animals and typically acts to repress genes (Bernstein et al, 2007), m6A is rarely found in metazoan genomes, and its existence and potential function remain unclear in human cells (Heyn and Esteller, 2015;O'Brown and Greer, 2016). The orthogonal properties of DNA adenine methylation were previously harnessed to develop technology for mapping chromatin-associated proteins in eukaryotic genomes (Kind et al, 2013;van Steensel and Henikoff, 2000).…”
Section: Introductionmentioning
confidence: 99%